2017
DOI: 10.1007/s12011-016-0929-3
|View full text |Cite
|
Sign up to set email alerts
|

The MMP-9/TIMP-1 System is Involved in Fluoride-Induced Reproductive Dysfunctions in Female Mice

Abstract: A total of 84 healthy female mice were kept with various concentrations of sodium fluoride (F) (0, 50, 100, 150 mg F/L in drinking water for 90 days) and were then mated with healthy male mice for 1 week to study the effect of excessive fluoride on female reproductive function, particularly in embryo implantation. The rate of pregnancy, litter size, and the birth weight of female mice were evaluated. Ultrastructural changes of uteri tissues were observed by transmission electron microscopy (TEM). The mRNA expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 42 publications
0
10
0
3
Order By: Relevance
“…Numerous studies have indicated that matrix metalloproteinases (MMPs), such as MMP‐2, MMP‐7, MMP‐9, and TIMP‐1, which mediate the process of extracellular matrix (ECM) remodeling, play a critical role in cell migration progress, and are a prerequisite for angiogenesis 56‐60 . Reynolds and Redmer 61 indicated that the formation of new blood vessels is requisite for placentation and MMPs can contribute to angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have indicated that matrix metalloproteinases (MMPs), such as MMP‐2, MMP‐7, MMP‐9, and TIMP‐1, which mediate the process of extracellular matrix (ECM) remodeling, play a critical role in cell migration progress, and are a prerequisite for angiogenesis 56‐60 . Reynolds and Redmer 61 indicated that the formation of new blood vessels is requisite for placentation and MMPs can contribute to angiogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Proteins were electrophoresed and then transferred to PVDF membranes. Immune complexes were detected with horseradish peroxidase‐conjugated secondary antibody (CWBIO, China) and visualized by enhanced chemiluminescence (Pierce, Appleton, Wisconin) . Antibodies used included TAU (66499‐1‐lg, Proteintech, Chicago, Illinois), SYP (17785‐1‐AP, Proteintech), DBN (10260‐1‐AP, Proteintech), and GAPDH (bsm‐0978M, Proteintech).…”
Section: Methodsmentioning
confidence: 99%
“…Independent‐samples t test was performed using IBM SPSS Statistics 20.0 for parametric data. A P value of <0.05 was considered significant …”
Section: Methodsmentioning
confidence: 99%
“…As we all know that F is necessary in lots of physiological activities. However, previous literatures have demonstrated that over-consumption of F not only damaged hard tissues, such as bone [3,4] and tooth [5,6], but also soft tissues, such as liver, kidney, thyroid, testis, uterus, and ovary [7][8][9][10][11]. Recently, literatures have suggested that over-intake F had intestinal toxicity [12,13], while the underlying mechanisms of the intestinal toxicity of F are unclear.…”
Section: Introductionmentioning
confidence: 99%